Prognostic significance of steroid response in pediatric acute lymphoblastic leukemia: The CCCG-ALL-2015 study - Chu, Jinhua; Cai, Huaju; Cai, Jiaoyang; Bian, Xinni; Cheng, Yumei; Guan, Xianmin; Chen, Xiaoqian; Jiang, Hua; Zhai, Xiaowen; Fang, Yongjun; Zhang, Lei; Tian, Xin; et al. (Frontiers in Oncology, 2022)
Whether hormonal response is an independent risk factor for acute lymphoblastic leukemia (ALL) is controversial.This study aimed to investigate the relationship between response to dexamethasone and prognosis in children with ALL.We analyzed the data of 5,161 children with ALL who received treatment in accordance with the Chinese Children's Cancer Group ALL-2015 protocol between January 1, 2015, and December 31, 2018, in China. After diagnosis, a 4-day dexamethasone prophase was maintained before induction therapy. The patients were classified into the dexamethasone good response (DGR) and dexamethasone poor response (DPR) groups. The age, white blood cell counts, prevalence of the BCR/ABL1 and TCF3/PBX1 fusion genes, and rates of recurrence in the central nervous system were higher in the DPR group than in the DGR group (P <0.001). Compared to the DPR group, the DGR group had a lower recurrence rate (18.6% vs. 11%) and higher 6-year event-free survival (73% vs. 83%) and overall survival (86% vs. 92%) rates; but subgroup analysis only showed significant difference in intermediate-risk group. (P<0.001). Response to dexamethasone was associated with an early treatment response in our study. In intermediate-risk group, dexamethasone response added prognostic value in addition to MRD which may direct early intervention to reduce relapse rate.